PROFESIONALISME APARATUR PEMERINTAHAN PADA KANTOR DINAS CATATAN SIPIL KABUPATEN KUTAI KARTANEGARA - Lukman Lukman (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2016)
Office of Population and Civil public service providers are required to work in a professional manner. Professionalism is the ability of the bureaucratic apparatus public in carrying out its duties and functions in an effective, responsive, innovative, and refers to the vision and mission of the organization. Pursuant to the definition used tersubut measurement indicators to see the professionalism of personnel and what factors can inhibit the professionalism of the apparatus.The study was conducted in 2008-2009 sepnajang with qualitative descriptive approach to answer the formulation of the research problem.Key word; professionalism, apparatus